Exploring the lambda model of the hybrid superstring - Schmidtt, David M. [UNESP] (Springer Nature, 2016)
The purpose of this contribution is to initiate the study of integrable deformations for different superstring theory formalisms that manifest the property of (classical) integrability. In this paper we choose the hybrid formalism of the superstring in the background AdS2 × S2 and explore in detail the most immediate consequences of its λ-deformation. The resulting action functional corresponds to the λ-model of the matter part of the fairly more sophisticated pure spinor formalism, which is also known to be classical integrable. In particular, the deformation preserves the integrability and the one-loop conformal invariance of its parent theory, hence being a marginal deformation.
Keywords: Integrable Field Theories; Sigma Models; Superstrings and Heterotic Strings